Kegiatan Pemetaan Potensi Desa dan Pembuatan Video Promosi Desa Petak Gianyar - I Made Bayu Wisnawa; I Ketut Sutapa; Luh Komang Candra Dewi; Gde Herry Sugiarto Asana; Dewiwati Sujadi; Made Christin Dwitrayani; I Dewa Ayu Tita Permata Tabita; Widya Kristanti; Valentien Natalya; Wiga Wiratama (Pubfine Media Group, 2024)
Petak Village is a village located in Gianyar District, Gianyar Regency. . Petak Village is located in the northern part of Gianyar City with a distance of 20 minutes or about 7 km from Gianyar City. Petak Village has 6 Banjars, namely, Banjar Benawah Kawan, Banjar Benawah Kangin, Banjar Bonnyuh, Banjar Madangan Kaja, Banjar Madangan Kelod and Banjar Umah Anyar. There are many tourism potentials owned by Petak Village, can be grouped as follows: natural tourism, artificial tourism, natural tourism, and culinary tourism. This dedication aims to divide the village so that the author knows the boundaries of the village area, and makes promotional videos about its tourism potential. With this activity, it is hoped that it can realize Petak Village to be more widely known by tourists and easy to access information about Petak Village.